Growth performance, nutrient utilization, rumen fermentation and enzyme activities in calves fed on Saccharomyces cerevisiae supplemented diet - KAMRA, D N; CHAUDHARY, L C; AGARWAL, NEETA; SINGH, R; PATHAK, N N (The Indian Journal of Animal Sciences, 2014)
To study the effect of dietary supplementation of yeast cells (YC) on body weight gain, nutrient digestibilities, production of ruminal metabolites and enzymes activities in the rumen, 16 crossbred cattle calves of 150.3Â± 14.3 kg live weight were used. The animals were distributed into 2 groups and fed 65% concentrate mixture and 35% wheat straw diet. Calves of the experimental group were given a daily dose (10 ml) of yeast cell suspension (YC) containing 5x109 cells/ml of Saccharomyces cerevisiae ITCCF 2094 for 159 days. There was no difference in the body weight gain, feed intake, feed conversion efficiency, digestibilities of nutrients and the nutritive value of diet between the groups. The activities of rumen enzymes, viz. carboxymethyl cellulase, amylase, xylanase, Î²-glucosidase, urease, aspartic and alanine transaminases were unaffected but protease was lower (P